The Role of Digital Literacy in Social Media - Isnaini, Isnaini; Nasyiriyah, Tiflatun Nasyiriyah; Aulia Istighfari, Novita; Rohmah, Susilatur Rohmah (Universitas Ahmad Dahlan, 2025)
The increasing spread of false information (hoaxes) in the post-truth era highlights the urgent need to enhance digital literacy. Digital literacy aims to empower audiences to critically interpret the vast array of messages circulating in digital media. This study explores the significance of digital literacy, its impact, and strategies for improving digital literacy skills to combat hoaxes. This research employs a library research method with a descriptive qualitative approach, analyzing a variety of relevant literature, including journals, books, and reports. The study focuses on the evolving media ecology and introduces novel insights into digital literacy, particularly in the Indonesian context. Findings reveal that the low level of digital literacy in Indonesia evidenced by a limited ability to critically analyze information contributes significantly to the widespread dissemination of hoaxes via social media. The study identifies five essential components of digital literacy: technical proficiency, critical thinking, visual literacy, social awareness, and adaptive skills. These components play a crucial role in enabling users to detect fake news, verify information, and minimize misinformation. Moreover, the research highlights the role of digital literacy as a sustainable solution for reducing hoaxes by fostering self-regulation and informed behavior. Recommendations include integrating digital literacy into educational curricula, conducting public awareness campaigns, and encouraging collaborative efforts between government and technology platforms. By addressing these challenges, this study contributes to a deeper understanding of digital literacy as a vital tool for navigating the complexities of the digital age and fostering a more informed society.